KETERAMPILAN BERBAHASA ARAB DENGAN PENDEKATAN KOMPREHENSIF - Lady Farah Aziza; Ariadi Muliansyah (El-Tsaqafah : Jurnal Jurusan PBA, 2020)
Comprehensive approach in teaching is a further implementationof the teaching plan that covers teaching procedure in detail. This researchaim to explore said comprehensive approach for Arabic language teachingthat focused in developing the four skills: listening (maharat al-istima’),speaking (maharat al-kalam), reading (maharat al-qira’at), and writing(maharat al-kitabah). This comprehensive approach consists of four steps:orientation, exploration, strengthening, and summarizing. Orientation isthe first step in the teaching process that encourages students to focus theirstudy on the subject presented. Exploration is the next step in the processthat encourages students to be active in finding the facts, problems, and itssolutions. Strengthening step is the process of deepening, broadening, andstrengthening the students’ skill and mastery of the subject obtained in theexploration step. The last step is summarizing, encourages the students topresent and summarize the subject they studied. Pembelajaran dengan pendekatan komprehensif merupakanlangkah implementasi dari rencana pembelajaran terpadu secara menyeluruh,berisi rincian dari prosedur pembelajaran. Penelitian ini bertujuan untukmengungkapkan bagaimana pendekatan komprehensif dalam pembelajaranbahasa Arab yang difokuskan untuk meningkatkan keterampilan berbahasaArab, seperti keterampilan mendengar (Maharat al-Istima’), keterampilanberbicara (Maharat al-Kalam), keterampilan membaca (Maharat al-Qira’at),keterampilan menulis (Maharat al-Kitabah). Ada empat langkah utamadalam pendekatan komprehensif ini yaitu, langkah orientasi, eksplorasi,pemantapan dan penyimpulan. Langkah orientasi atau kegiatan awalpembelajaran merupakan langkah untuk mendorong kelas memusatkanperhatian terhadap pembelajaran; langkah eksplorasi adalah langkah untukmengajak dan mendorong siswa untuk mencari dan menemukan fakta,pengetahuan, masalah dan pemecahan; langkah pemantapan merupakanlangkah memperdalam, memperluas, memantapkan, memperkuatpenguasaan materi dan kemampuan yang telah dicapai pada langkaheksplorasi; dan langkah penyimpulan adalah langkah untuk menyimpulkantentang apa yang telah dipelajari.